Reform of psychiatric care in Brazil: reality and perspective - Adriana da Cunha Menezes Parente, Luciana da Cunha Menezes, Fernanda Matos Fernandes Castelo Branco, Jaqueline Carvalho e Silva Sales, Alexandre Castelo Branco Vaz Parente (Revista de Enfermagem da UFPI)
DOI: https://doi.org/10.26694/reufpi.v2i2.788